(untitled) (Research, Society and Development, 2020)
With the new social-economic contemporary perspectives it is possible to evaluate the employees’ accounts about the functional demands, which highlight the existence of psychological damages, including moral harassment. This issue interferes in the functional development and productivity, especially when it comes to the organization-work-health relationship. The present article aims at checking the psychometric quality of the moral harassment scale at work with professionals from the education and health areas from a town in the countryside of the state of Paraíba, Brazil, with the participation of two hundred employees, among men and women, aged between 19 and 64 years (M = 41.56, s.d. = 12.08). Most of the respondents presented an income between 1 and 2 minimum wages and a period of employment ranging from 1 to 36 years (M = 10.77, s.d. = 8.93). Their answers include a perception scale of moral harassment at work, a Moral Harassment Affective Impact scale at work and social-demographic data. The results show that the constructs used were trustworthy, confirm the moral harassment evaluation, and that this is an existing phenomenon, no matter the respondents’ work sector. Such results offer some safety to the measure in question. They are also a diagnostic tool for human resources to follow up on the organization-work-health dynamics.